Marketing Analysis Strategy Organic Rice at UD. Padi Marketing Region Bekasi with Single Agent (Yasin Holistic Super Organic) - Euis Dasipah; Is Zunaini Nursinah; Taryadi Taryadi (International Journal of Nusantara Islam, 2013)
Organic food (organic rice) actually is not something new for Indonesian people. Before "Green Revolution" (1960th), Indonesian farmers have produced rice without using chemical pest and fertilizer (conventional rice). Holistic Super Organic (HSO) rice is one of the brand organic rice, which is sold in Indonesia's market. Usaha Dagang (U.D. Padi) is the company, which is special to produce, and marketing HSO rice. The research is wanted to know marketing strategy HSO rice, especially in district of Bekasi with SWOT analysis. This research used case study methods with held by interview and literature study. The result of analyzing identified that the strengths from U.D. Padi was dominant and the opportunities so on. So, the next plan of marketing's strategy for is Aggressive Strategy. Aggressive Strategy is the effort to maximalize the strengths to get the opportunities optimally. The strengths of U.D. Padi is the especially of product and the distribution strategy which was held with excellent. The opportunities U.D. Padi is the wealth people who was increasing and the distributor channel who was welcome.